An interesting case of cutaneous horn (Indian Journal of Case Reports, 2019)
Cutaneous horn is an uncommon lesion consisting of keratotic material and a clinical diagnosis referred to as, a conical projection of cornified material above the surface of the skin that resembles a miniature horn. The horn is composed of compacted keratin. Cutaneous horns usually develop on a keratinocyte base with the histopathology on a spectrum ranging from benign keratosis to invasive squamous cell carcinoma. Here, we report the case of a cutaneous horn in a 65-year-old male.